Effect on summer stocker gains when native grass pastures were either grazed short during the dormant season or burned in April - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1993)
Four hundred and ten mixed-breed heifers were intensively early grazed for 81 days on native tall grass pastures where dormant growth had been removed by either winter grazing or April burning. Heifers grazing the burned pastures gained .19 lb/day more (1.99 vs 1.80 lb; P<.05) than those grazing pastures that had the dormant grass removed by heavy grazing during February and March.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Burning; Stocker cattle; Native grass